‘In-formation’ of Better Learning Environments - the Educational Role of the University Library - Hapke, Thomas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
This paper gives an overview of the close connection between learning - which is seen as a constructivist, active, self-directed and social process - and the university library. It discusses the role of the university library in the electronic learning environment, and considers the physical library as a place of learning which is not out of date. It also considers information literacy as the key to the library's educational role regarding its contents. Organisational issues hold together the three points mentioned above, the learning library as the prerequisite of the learning-empowering and learning-facilitating library.